Pengaruh Penerapan Sistem E-Filling dan Peran Account Representative Pada Kepatuhan Wajib Pajak Orang Pribadi - Suratningsih, Ni Putu; Merkusiwati, Ni Ketut Lely Aryani (E-Jurnal Akuntansi; Vol 24 No 2 (2018)DO - 10.24843/EJA.2018.v24.i02.p15, 2018)
Implementation of e-Filling system makes it easier for taxpayers to report online tax returns. Based on the Account Representative (AR) function expected taxpayers submissive in reporting the tax return. The purpose of this study is to determine the empirical evidence whether there is influence the application of e-Filling system and Account Representative to the taxpayer compliance Person. This research uses quantitative method. The sample used in this research is Individual Taxpayer Registered In Tax Office Pratama East Denpasar. The sampling technique used incidental sampling method. Sources of data were obtained through questionnaires and used multiple linear regression analysis techniques. The results showed that the application of e-Filling Implementation system had a positive effect on taxpayer personal compliance in KPP Pratama East Denpasar, while the role of Account Representative has no effect on Personal Taxpayer Compliance in KPP Pratama East Denpasar. Keywords: E-filling System, Account Representative, Personal Taxpayer Compliance